SALES GROWTH, EARNINGS VOLATILITY, AND GREEN ACCOUNTING ON STOCK PRICES (EVIDENCE FROM INDONESIA’S NON-CYCLICALS CONSUMER SECTOR) - Adi, Maria Paramastri Hayuning; Suroso, Amin; Suci, Patricia Paramitha (Universitas PGRI Semarang, 2024)
This research aims to examine the indicators that determine stock prices. This study uses sample data in the form of 114 company data in the consumer non-cyclical sector listed on the Indonesia Stock Exchange during 2020-2022. These companies were chosen because Indonesia was affected by the Covid-19 pandemic and companies in this sector were categorized as fairly stable companies so investors were interested in their shares. The indicators used are sales growth, profit volatility, and green accounting. The analysis method used is multiple linear regression analysis using SPSS 29 software. The results of this study indicate that profit volatility has a significant effect on stock prices. In contrast, sales growth and green accounting do not have a substantial effect on stock prices. It is recommended to include additional indicators in various business sectors for further research. Keywords :Â Corporate Sustainability; Green Accounting; Sales Growth; ProfitabilityÂ